2012
DOI: 10.1371/journal.pone.0046921
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Hippocampal BDNF and miR-16 Expression Is Associated with Depression-Like Behaviors Induced by Stress during Early Life

Abstract: Some environmental stressors lead to the onset of depression via inhibiting hippocampal BDNF expression, but other environmental stressors-induced depression exhibits no change in BDNF expression. The underlying mechanisms behind the divergence remain unknown. In this study, depression-like behaviors were induced in rats by maternal deprivation (MD) and chronic unpredictable stress (CUPS). Depression-like behaviors were tested by open field test, forced swimming test, and sucrose consumption test. BDNF and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 32 publications
9
123
0
Order By: Relevance
“…25 While specific upstream regulators of cortical miR16 expression have yet to be investigated, damaging DNA increases miR16 expression in human fibroblasts 48,49 and maternal deprivation increases miR16 in the hippocampus. 50 Although our findings are consistent with miR16 as an upstream factor accounting for lower RGS4 levels in schizophrenia, RGS4 levels can be lowered through other mechanisms. For example, genetic ablation of brain-derived neurotrophic factor (BDNF) during adulthood reduces RGS4 levels, 51 and findings consistent with lower BDNF signaling in the DLPFC have been reported in schizophrenia.…”
Section: Discussionsupporting
confidence: 83%
“…25 While specific upstream regulators of cortical miR16 expression have yet to be investigated, damaging DNA increases miR16 expression in human fibroblasts 48,49 and maternal deprivation increases miR16 in the hippocampus. 50 Although our findings are consistent with miR16 as an upstream factor accounting for lower RGS4 levels in schizophrenia, RGS4 levels can be lowered through other mechanisms. For example, genetic ablation of brain-derived neurotrophic factor (BDNF) during adulthood reduces RGS4 levels, 51 and findings consistent with lower BDNF signaling in the DLPFC have been reported in schizophrenia.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies reported that merely 37–50% of individuals diagnosed with depression experience clinically significant anhedonia (Bogdan, Nikolova, & Pizzagalli, 2013; Pelizza & Ferrari, 2009). Our previous study in rats also demonstrated that the depressive phenotype induced by maternal deprivation (MD), a well‐verified depressogenic stressor, was characterized by severe anhedonia while the depressive phenotype triggered by chronic unpredictable stress (CUPS), another well‐established depressogenic stressor, primarily exhibited anxiety and passive coping behavior (Bai et al., 2012; Bai, Zhang, et al., 2014; Bai, Zhu, et al., 2014). However, the precise neurobiological basis of different depressive phenotypes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of fluoxetine into the raphe nucleus, a major source of ascending serotonergic projections in the brain, resulted in a decrease in miR-16 and a two-fold reduction in binding of serotonin transporter (Baudry et al, 2010). Fluoxetine applied at the raphe, also appears to affect miRNA expression in the locus coeruleus (Baudry et al, 2010) and hippocampus (Launay et al, 2011) causing a reduction in miR-16 and a subsequent increase in serotonin transporter levels in both brain regions. Furthermore, neutralisation of miR-16 in the hippocampus by application of anti-miR16 results in antidepressant-like behavioural effects highlighting the importance of its role in the downstream effects of fluoxetine (Launay et al, 2011).…”
Section: Tablementioning
confidence: 97%
“…Studies examining the expression of miR-16, which targets the serotonin transporter, have provided insight into the mechanism of action of fluoxetine in the mouse brain (Baudry et al, 2010;Launay et al, 2011). Infusion of fluoxetine into the raphe nucleus, a major source of ascending serotonergic projections in the brain, resulted in a decrease in miR-16 and a two-fold reduction in binding of serotonin transporter (Baudry et al, 2010).…”
Section: Tablementioning
confidence: 99%